Extraction and characterization of glycerides from oilseed of Pongamia pinnata plant found in Manipur: EXTRACTION AND CHARACTERIZATION OF GLYCERIDES FROM PONGAMIA PINNATA IN MANIPUR - MD ABDUL HALIM SHAH; NAOREM SHUBHASCHANDRA SINGH (Journal of Oilseeds Research, 2024)
The extraction of Pongamia pinnata seed oil was accomplished through the solvent extraction technique, employing petroleum ether as the solvent on the crushed kernel. Subsequent to extraction, the oil underwent purification for further analysis via column chromatography over silica gel (60-120 mesh), utilizing a mixture of petroleum ether and ethyl acetate (20:1) as the eluent. The resulting purified oil was then subjected to transesterification, producing the final product recognized as biodiesel, characterized by its composition of fatty acid methyl ester (FAME). The FAME composition of Pongamia pinnata seed oil was meticulously determined through NMR, IR, and GC-MS analyses. The transesterified oil of Pongamia pinnata revealed a FAME composition consisting of 10.53 wt% of methyl palmitate (C16:0), 68.05 wt% of methyl oleate (C18:1), 12.58 wt% of methyl stearate (C18:0), 3.65 wt% of methyl arachidate (C20:0), and 5.22 wt% of methyl behenate (C22:0).